Will things feel better in the morning? A time-of-day analysis of mental health and wellbeing from nearly 1 million observations - Daisy Fancourt; Feifei Bu; Jessica K Bone (BMJ Mental Health)
Background Mood is known to change over seasons of the year, days of the week, and even over the course of the day (diurnally). But although broader mental health and well-being also vary over months and weeks, it is unclear whether there are diurnal changes in how people experience and report their mental health.Objective To assess time-of-day association with depression, anxiety, well-being and loneliness.Methods The study analysed data from 49 218 adults drawn from the University College London COVID-19 Social Study, which gathered detailed repeated measurements from the same participants across time over a 2-year period (March 2020–March 2022, 18.5 observation per person). Data were analysed using linear mixed-effects models.Findings There is a clear time-of-day pattern in self-reported mental health and well-being, with people generally waking up feeling best and feeling worst around midnight. There is also an association with day of the week and season, with particularly strong evidence for better mental health and well-being in the summer. Time-of-day patterns are moderated by day, with more variation in mental health and individual well-being during weekends compared with weekdays. Loneliness is relatively more stable.Conclusions Generally, things do seem better in the morning. Hedonic and eudemonic well-being have the most variation, and social well-being is most stable.Clinical implications Our findings indicate the importance of considering time, day and season in research design, analyses, intervention delivery, and the planning and provision of public health services.